A cross cultural study of motor development in the Western Cape - Irwin-Carruthers, Sheena Margaret Hamilton (Department of Paediatrics and Child Health, 2018)
Despite conflicting evidence regarding advanced motor behaviour in black African infants, very few comparative studies have been published. Reliable developmental norms for local populations are essential for the early identification of developmental disabilities. In this study the sample consisted of 681 black and 741 white infants drawn proportionally from the Child Health Care Clinics in the northern areas of greater Cape Town. Babies were sampled in specified age-intervals between the ages of 16 and 1170 days. Variables studied were sex, birth-ranking, weight-percentile at the time of testing, marital status of the mother, parents' education and occupation, family size and family income. The demographic characteristics of the sample were compared with those of the population as a whole, based upon the 1980 census. The testing instruments were the gross and fine motor-adaptive sections of the Denver Developmental Screening Test, supplemented by another 21 items representing reflex reactions or specific components of movement. These supplementary items were pre-tested for inter- and intra-observer reliability. The percentage of children responding to the different tests at different ages was determined by probit analysis or, where more appropriate, by non-parametric logistic regression. Differences between the black and white South African infants were subjected to further statistical analysis, as was the contribution of the different variables to the attainment age. Comparison of the performance of the South African infants with the Denver norms showed that both black and white babies were in advance of the Denver children on the majority of fine motor items. The black infants were also considerably advanced in gross motor behaviour; the white infants less markedly so. In the very few (3) items in which the Denver children excelled, doubts exist regarding either scoring criteria or cultural suitability. Comparative analysis of the two South African samples identified certain consistent developmental trends. The black infants performed better on basic grasping patterns whereas the white infants were advanced in manipulative skills. The black infants were advanced on gross motor behaviour in the first year but were overtaken by the white group on learned gross motor skills in the second and third year, with the exception of items requiring physical strength. Very little correlation could be shown between motor achievement and socio- economic factors. Differences appear to be largely due to child-handling practices and experiential learning, but ethnic characteristics may well play a role in the advanced early gross motor development of the black infant. Heavier infants also performed better in both groups, indicating nutritional influences. The clinical implications of the findings are discussed and recommendations made for implementation and for further research.